2021
DOI: 10.3390/molecules26206131
|View full text |Cite
|
Sign up to set email alerts
|

K-Carrageenan Stimulates Pre-Osteoblast Proliferation and Osteogenic Differentiation: A Potential Factor for the Promotion of Bone Regeneration?

Abstract: Current cell-based bone tissue regeneration strategies cannot cover large bone defects. K-carrageenan is a highly hydrophilic and biocompatible seaweed-derived sulfated polysaccharide, that has been proposed as a promising candidate for tissue engineering applications. Whether κ-carrageenan can be used to enhance bone regeneration is still unclear. In this study, we aimed to investigate whether κ-carrageenan has osteogenic potential by testing its effect on pre-osteoblast proliferation and osteogenic different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Moreover, it has been shown that sulfated polymer grafting onto a scaffold surface increases the secretion of fibronectin and collagen by osteoblasts (Pavon-Djavid et al, 2007). The Frontiers in Bioengineering and Biotechnology frontiersin.org sulfated polysaccharide ĸ-Car promotes paxillin protein expression by pre-osteoblasts (Cao et al, 2021). Protein adsorption on a scaffold surface promotes cell adhesion, proliferation, and osteogenic differentiation (Gandavarapu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it has been shown that sulfated polymer grafting onto a scaffold surface increases the secretion of fibronectin and collagen by osteoblasts (Pavon-Djavid et al, 2007). The Frontiers in Bioengineering and Biotechnology frontiersin.org sulfated polysaccharide ĸ-Car promotes paxillin protein expression by pre-osteoblasts (Cao et al, 2021). Protein adsorption on a scaffold surface promotes cell adhesion, proliferation, and osteogenic differentiation (Gandavarapu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Glycosaminoglycan (GAG)-like anionic polysaccharides are also widely used for biomaterial functionalization, because of their ability to facilitate cell adhesion, proliferation, and differentiation (Malliappan et al, 2022). Among several kinds of anionic polysaccharides, carboxymethyl cellulose (CMC; a plant-based carboxymethylated polysaccharide) (Seddiqi et al, 2021), and κcarrageenan (a seaweed-derived sulfated polysaccharide) (Cao et al, 2021) have attracted attention for tissue engineering applications. The ease of chemical functionalization, hydrophilicity, favorable mechanical properties, and biocompatibility make CMC and κcarrageenan interesting for tissue engineering applications (Cao et al, 2021;Zennifer et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The attached number of cells was considered to represent cell adhesion. The surface area of cells was considered to quantitatively represent cell spreading [ 74 , 75 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition to wound healing applications, K-carrageenan presents remarkable results in the field of regenerative medicine [ 124 ]. Thus, K-CG has been reported to have osteogenic potential because it induced the metabolic activity of pre-osteoblast cells [ 125 ]. Silk fibroin/K-CG electrospun nanofibers showed great osteogenic properties [ 126 ].…”
Section: Carrageenans: Structure Types and Wound Healing Effectsmentioning
confidence: 99%